Explosion of metastable droplets in immiscible liquids. (December 2021) - Rebelo, N.; Nadal, F.; Garner, C.P.; Zhao, H.
Highlights: Droplets can explode incompletely in immiscible liquids above the superheat limit. Incomplete explosion of a droplet can produce a 'film evaporation' configuration. Complete droplet explosion requires the global Jacob number J a ≥ 1 . The difference between the experimental and theoretical superheat limit is ≤ 1.5 K. Abstract: Evaporation of metastable droplets in an immiscible liquid can occur in a wide range of practical applications and in particular in cryogenic systems due to the low saturation temperature of the cryogenic liquid. In this article, we show experimentally that the incomplete explosion of a metastable droplet can lead to a 'film evaporation' configuration, where a remaining droplet is eventually separated from the host immiscible liquid by an established vapour layer. Based on a transient heat diffusion model, we identified that the necessary but not sufficient condition for the complete explosion of a metastable droplet is that the droplet must absorb, before explosion, an amount of heat larger than the latent heat required for a full evaporation, i.e. the global Jacob number J a ≥ 1 . In addition, the measured superheat limits of pentane and isohexane are 420.65 K and 444.95 K respectively, which are very close to the theoretical Spinodal points ( ≤ 1.5 K) and other reported values in existing literature. Therefore, the experimental setup reported here can be used as an alternative way to quantify the superheat limit. The Droplet relaxation time was also found scaled to the square root of the diffusion characteristic time.